Nanofluidic ion tunnel diode and testing device and method thereof
By developing nanoflow ion tunnel diodes, using heterostructured nanotube arrays and flexible polymers, a negative linear increase in ion current is achieved under linearly growing voltages, solving the problems of high energy consumption and functional bottlenecks of tunnel diodes in the prior art, and has broad potential for brain-like computing applications.
Patent Information
- Application Number
- CN202311200763.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing electronic computing systems have high energy consumption problems when processing information and transmitting data, and tunnel diodes based on solid-state materials have reached a bottleneck in the electronic computing function, and the negative linear increase in ion current cannot be achieved.
A nanoflow ion tunnel diode is developed, a nanotube vertical array with heterostructured treatment is used to fill the nanotube gap with flexible polymer, and asymmetrically deform the nanotube array through a pressure deformation device to achieve a negative linear increase in ion current under a linearly increasing voltage.
It realizes multiple voltage values corresponding to the same ion current, has potentially applied to the new generation of brain-like nanofluid computing system, and is a flexible structure, easy to maintain and adapt to different interfaces.
Smart Images

Figure HDA0004454002660000011 
Figure HDA0004454002660000012 
Figure HDA0004454002660000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of micro-nano processing technology and bionic nanocurrent ionics, and relates to a novel nanocurrent ion tunnel diode and a testing device and method thereof. Background Art
[0002] Although existing digital computing based on the von Neumann computing architecture can perform artificial intelligence tasks, the number of electronic components required to process information and transmit data is very large, resulting in intensive energy consumption. The shift of digital computing from computing and storage to pattern recognition and other artificial intelligence tasks has also driven the demand for more energy-efficient architectures. In digital computing, electrons are carriers in circuits, while in biological systems, ions are carriers of information transmission and have unique advantages (there will be no cancellation of holes and electrons, the types and chemical properties of ions are diverse, and they can provide stronger encoding and parallel computing capabilities. The mass of ions with the same charge is much greater than the mass of electrons with the same charge, and they can better resist various external electromagnetic interference). The power consumption of each person's brain during complex calculations is only tens of watts, which is far less than the energy consumption of an ordinary electronic computer.
[0003] Therefore, in the face of the von Neumann bottleneck of traditional electronic computing systems, people hope to use this type of device to simulate the computing mode of the brain and realize a series of brain-like computing functions from the hardware, such as parallel computing, pattern recognition, and artificial neural network construction. With the development of brain science, people have a deeper understanding of the ultra-low energy consumption physiological process of the brain in the process of calculation and memory. The neural signals in the human brain are transmitted through action potentials, and the generation of action potentials is inseparable from the regulation of ion transmission in the nano-confined space of the ion channels in the neuronal cells. Nanofluidics, as a technology for studying the behavior of fluids in nano-confined spaces, has achieved rapid development in the past decade. Inspired by the generation and storage mechanism of neural signals in the brain, bionic nanofluidics is an emerging interdisciplinary subject born against the background of the rapid maturity of micro-nano processing technology. It has become a tool that combines electronic properties and ion current signal processing. By designing the nano-confined space system with the help of micro-nano processing technology, it can realize the intelligent regulation of the transmission behavior of ions and other fluids inside it. It has broad application prospects in interdisciplinary fields such as artificial intelligence, flexible brain-computer interface, brain-like intelligence and human-computer enhancement.
[0004] In digital electronic computers, tunnel diodes are one of the most important electronic components. The special thing about them is that the relationship between their current and voltage is different from that of ordinary diodes. The current-voltage characteristic curve of tunnel diodes has a "negative correlation" area, which is often used in high-speed switches and low-noise amplifiers. They can be used to design high-speed circuits, such as clock circuits, counters, shift registers, etc. In addition, tunnel diodes can also be used to design analog circuits such as high-speed analog-to-digital converters, digital-to-analog converters, and analog-to-digital converters, as well as circuits for radio frequency signal detection and modulation. In addition, tunnel diodes can also be used in high-frequency oscillators, frequency multiplexers and other fields. In short, tunnel diodes play an important role in computers, providing a high-efficiency and high-speed operating basis for computers.
[0005] At present, the electronic computing functions of all tunnel diodes are realized through solid-state devices such as metal oxides. The development of electronic transmission devices based on these solid-state materials has also encountered bottlenecks, and nanocurrent devices based on ion transmission can still only achieve the current-voltage "positive correlation" characteristics. For the development of ion computing systems involved in the emerging bionic nanocurrent ionics, it is necessary to form a set of algorithms and components that can adapt to this new type of nanocurrent ion computing. Therefore, the development of nanocurrent ion tunnel diodes also plays an important role. However, there are no relevant literature reports on nanocurrent ion tunnel diodes based on ion transmission. Summary of the invention
[0006] The main purpose of the present invention is to provide a nanocurrent ion tunnel diode.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] One of the purposes of the present invention is to provide a nanocurrent ion tunnel diode having a heterogeneous structured nanotube array, wherein the nanotube vertical array has a nanocurrent channel, and the nanocurrent channel has ions, so that a negative linearly increasing ion current is obtained under a linearly increasing voltage.
[0009] Furthermore, a plurality of voltage values can correspond to the same ion current.
[0010] Another object of the present invention is to provide a novel method for testing a nanocurrent ion tunnel diode, which mainly comprises the following steps:
[0011] (1) Preparation of heterostructured nanotube vertical arrays;
[0012] (2) Filling the gaps between the vertical arrays of nanotubes with flexible polymers;
[0013] (3) asymmetric deformation of the vertical nanotube array by a pressure deformation device;
[0014] (4) Conduct nanocurrent ion transport testing using an external static ion transport test system;
[0015] Optionally, the heterostructured treatment method described in step (1) includes but is not limited to high temperature heat treatment, hydrothermal treatment, plasma etching, electrodeposition and the like; the heterostructured reagent includes but is not limited to melamine, urea, thiourea, selenium disulfide / tin diselenide complex and the like containing one or more non-metallic or non-metallic elements such as N, O, S, P, Sn, etc.; the ratio of the heterostructured reagent to the nanotube vertical array is between 1 and 10; the nanotube vertical array includes but is not limited to carbon nanotube vertical array, boron nitride nanotube vertical array, silicon carbide nanotube vertical array and the like, and its geometric structure may change; the deposition method of the nanotube vertical array includes but is not limited to floating catalytic chemical vapor deposition, plasma enhanced chemical vapor deposition, arc discharge, laser ablation and the like, and its deposition thickness is between 20 microns and 1000 microns; the pore size of the nanotube vertical array is between 1 nanometer and 100 nanometers.
[0016] Optionally, the flexible high molecular polymer in step (2) may be, but is not limited to, polydimethylsiloxane, epoxy resin, polyamide resin, silica gel, etc., which has a certain elastic modulus and good wettability to the nanotubes. The density of the gaps in the vertical array of nanotubes should be at least 10 7 roots / per square centimeter or more.
[0017] Optionally, the pressure deformation device described in step (3) includes a pressure sensor, a polytetrafluoroethylene electrolytic cell tank capable of storing a solution, and a spiral-driven pressure application module.
[0018] Optionally, the external static ion transport test system described in step (4) includes a silver / silver chloride (Ag / AgCl) electrode, which should have the following characteristics: reversibility: current can be conducted in both directions; when conducting current for a long time, especially when a large current is conducted, the AgCl at the negative electrode will be consumed and needs to be electroplated regularly; Cl - Dependence: Ag / AgCl electrode must be in the presence of Cl -ions (at least 10mmol / L). The ion solution includes but is not limited to NaCl, NaBF4, MgCl2, KCl, FeCl3, ionic liquids, etc.; the concentration of the ion solution is selected from 0.1mmol / L to 1mol / L. The test method includes but is not limited to linear sweep voltammetry, cyclic voltammetry, constant voltage pulse scanning, alternating electric field scanning voltammetry (sinusoidal voltage, square wave voltage, triangle wave voltage, etc.), and the voltage selection range is between 10mV and 1000mV. The geometric structure of the nanochannel undergoes asymmetric changes during the test, and the applied pressure is between 100N and 500N.
[0019] Another object of the present invention is to provide a nanocurrent ion transport system testing device, comprising two electrolytic cell tanks capable of storing solutions, a heterostructured nanocurrent channel sandwiched between the two electrolytic cell tanks, and a through hole provided on the contact surface of the electrolytic cell tanks and the heterostructured nanocurrent channel, so that the solutions between the electrolytic cell tanks and the heterostructured nanocurrent channel can communicate with each other; a left chamber and a right chamber respectively have electrodes; a pressure sensor is provided on a side of one electrolytic cell tank away from the nanocurrent channel, and a pressure application module is provided on a side of the other electrolytic cell tank away from the nanocurrent channel; and an ion solution is provided in the electrolytic cell tank.
[0020] Furthermore, a constant temperature water bath is provided in each of the two electrolytic cells.
[0021] Furthermore, the pressure applying module is a spiral-pushed pressure applying module.
[0022] The beneficial effects of the present invention are:
[0023] ① The present invention constructs a nanoflow ion transport system of heterogeneous structured nanoflow channels, and utilizes the chemical property asymmetry and geometric structure asymmetry of heterogeneous structured nanochannels to realize the preparation of a new type of nanoflow ion tunnel diode based on solution ions, and develops its performance test method;
[0024] ② The novel nanocurrent ion tunnel diode involved in the present invention can achieve a negative linearly increasing ion current under a linearly increasing voltage. It can correspond to multiple voltage values under the same ion current and has the potential value of being applied to the ion tunnel diode in the new generation of brain-like nanofluid computing systems.
[0025] ③ The novel nanocurrent ion tunnel diode involved in the present invention is different from the traditional rigid structure silicon-based electronic devices. It has a flexible structure, simple structure, easy maintenance, can be adapted to any interface, and can also be used in life systems containing physiological solutions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0027] Figure 1 Schematic diagram of the test device of the nanoflow ion transport system for heterogeneous structured nanoflow channels. In the figure, 1 is the Ag / AgCl electrode; 2 is the solution injection channel; 3 is the heterogeneous structured nanoflow channel; 4 is the pressure sensor; 5 is the polytetrafluoroethylene electrolytic cell; 6 is the constant temperature water bath; 7 is the spiral push pressure application module.
[0028] Figure 2 Schematic diagram of the test mechanism of nanocurrent ion tunnel diode based on heterostructured nanocurrent channel.
[0029] Figure 3 This is the current-voltage result diagram of the heterostructured nanochannel obtained by linear sweep voltammetry test, which can obtain a negative linearly increasing ion current under a linearly increasing voltage.
[0030] Figure 4 This is the current-voltage result diagram of the heterostructured nanochannel tested by the constant voltage pulse scanning method. Under the constant voltage positive and negative alternating pulses, a negative linearly increasing ion current can be obtained.
[0031] Figure 5 This is the current-voltage result diagram of the untreated nanochannel obtained in the linear sweep voltammetry test, which can obtain a positive linearly increasing ion current under a linearly increasing voltage.
[0032] Figure 6 This is a current-voltage result diagram of an untreated nanochannel tested by a constant voltage pulse scanning method. Under a constant voltage positive and negative alternating pulse, a negative linearly increasing ion current can be obtained. DETAILED DESCRIPTION
[0033] like Figure 1 As shown, the nanoflow ion transport system test device includes two polytetrafluoroethylene electrolytic cells 5 that can store solutions, respectively referred to as the left chamber and the right chamber, and the heterogeneous structured nanoflow channel 3 is sandwiched between the left chamber and the right chamber, and through holes are provided on the contact surfaces of the left chamber, the right chamber and the heterogeneous structured nanoflow channel 3, so that the solutions between the left chamber, the heterogeneous structured nanoflow channel 3 and the right chamber can communicate with each other. A constant temperature water bath 6 is provided in the left chamber and the right chamber, respectively, which can heat the left chamber and the right chamber. The left chamber and the right chamber have Ag / AgCl electrodes 1 and solution injection channels 2, respectively.
[0034] The left side of the left chamber is provided with a pressure sensor 4, and the right side of the right chamber is provided with a spiral push pressure applying module 7. After the nanocurrent ion transmission system test device is assembled, the whole is placed in a base with a length and width similar to the device for use.
[0035] Example 1
[0036] First, using toluene and ferrocene as carbon sources (ferrocene also functions as a catalyst), a vertical array of carbon nanotubes is deposited on a silicon dioxide substrate by floating catalytic chemical vapor deposition, and the diameter of the obtained vertical array of carbon nanotubes is about 5 nanometers to 80 nanometers. Further, melamine is used as a precursor to perform heterogeneous structural treatment of the vertical array of carbon nanotubes through high-temperature heat treatment. The mass ratio of melamine / vertical array of carbon nanotubes is about 3:1. Through programmed temperature rise, it is treated at a low temperature of 300℃ to 700℃ for 2 hours, so that N atoms further enter the graphite lattice structure of the carbon nanotubes, causing the chemical properties of the vertical array of carbon nanotubes to change asymmetricly. Furthermore, flexible high molecular polymers (epoxy resin, polyamide resin, dimethyl phthalate) were selected and cured and packaged for the carbon nanotube vertical array in a ratio of 1:0.9:0.72. An ultrathin slicer was used to open the carbon nanotube nanoflow channels at both ends of the carbon nanotube vertical array. At the same time, in an air atmosphere, at a power of 100 watts, the sliced carbon nanotube nanoflow channels were plasma treated for 120 seconds.
[0037] Place the treated carbon nanotube nanofluidic channel as shown in the attached Figure 1 In the device, homemade Ag / AgCl electrodes were inserted into the left and right chambers of the device respectively, and 1mmol / L potassium chloride solution was injected. At the same time, the pressure sensor was used to apply a pressure of about 100N to 500N in real time by spirally pushing the pressure application module, so that the geometric structure of the carbon nanotube nanoflow channel changed asymmetrically. At the same time, an electrochemical workstation was used to collect ion current in real time through the electrodes. The schematic diagram of the test mechanism is shown in the attached figure. Figure 2 As shown. With the application of pressure, the asymmetry of the geometric structure and chemical properties of carbon nanotubes is further highlighted. Ions in the nanofluidic channel of carbon nanotubes will be hindered and adsorbed / desorbed by the built-in electric field generated by them. Linear sweep voltammetry is used to apply different sweep voltages (between -10mV ~ +10mV and -1000mV ~ +1000mV), and a negative linear increase in ion current is obtained under a linearly increasing voltage. The test results are shown in the attached Figure 3 As shown. The constant voltage pulse scanning method is used to apply voltage (the pulse voltage is between ±10mV and ±1000mV, and the interval time is between 10ms and 1000ms). Under the constant voltage positive and negative alternating pulses, a fluctuating negative linear increasing ion current can be obtained. The test results are shown in Figure 4 shown.
[0038] Example 2
[0039] First, using iron oxide and amorphous boron powder as raw materials, at a temperature of 1300°C, a vertical array of boron nitride nanotubes is deposited by chemical vapor deposition, and the diameter of the obtained vertical array of boron nitride nanotubes is about 20 nanometers to 60 nanometers. Further, melamine is used as a precursor to carry out heterogeneous structural treatment of the vertical array of carbon nanotubes through high-temperature heat treatment. The mass ratio of melamine / carbon nanotube vertical array is about 3:1. Through programmed temperature rise, it is treated at a low temperature of 300°C to 700°C for 2 hours, so that N atoms further enter the graphite-like plane hexagonal mesh structure of the boron nitride nanotubes, causing the chemical properties of the vertical array of boron nitride nanotubes to change asymmetrically. Furthermore, a flexible high molecular polymer (polydimethylsiloxane) was selected to solidify and encapsulate the vertical array of boron nitride nanotubes at a ratio of 10:1, and an ultrathin slicer was used to open the boron nitride nanotube nanoflow channels at both ends of the vertical array of boron nitride nanotubes. At the same time, in an air atmosphere, the sliced boron nitride nanoflow channels were plasma treated for 120 seconds at a power of 100 watts.
[0040] The treated boron nitride nanotube nanoflow channel was placed in the test device, and homemade Ag / AgCl electrodes were inserted into the left and right chambers of the device, and 1mmol / L potassium chloride solution was injected. Different sweeping voltages (between -10mV~+10mV and -1000mV~+1000mV) were applied by linear sweep voltammetry. At the same time, through the pressure sensor, the pressure application module was pushed by the spiral to apply a pressure of about 100N~500N in real time, so that the geometric structure of the boron nitride nanotube nanoflow channel changed asymmetrically. At the same time, the electrochemical workstation was used to collect ion current in real time through the electrode. With the increase of applied pressure, the asymmetry of the geometric structure and chemical properties of the boron nitride nanotube was further highlighted. The ions in the boron nitride nanotube nanoflow channel will be hindered and adsorbed / desorbed by the built-in electric field generated by it, and the negative linear increase of ion current can also be obtained under the linear increase of voltage. The voltage is applied by constant voltage pulse scanning method (the pulse voltage is between ±10mV and ±1000mV, and the interval time is between 10ms and 1000ms). Under the constant voltage positive and negative alternating pulses, a fluctuating negative linear increasing ion current can also be obtained.
[0041] Example 3
[0042] First, using toluene and ferrocene as carbon sources (ferrocene also functions as a catalyst), a vertical array of carbon nanotubes was deposited on a silicon dioxide substrate by floating catalytic chemical vapor deposition, and the diameter of the obtained vertical array of carbon nanotubes was about 5 nanometers to 80 nanometers. Further, using selenium disulfide / tin diselenide complex as a precursor, the carbon nanotube vertical array was subjected to heterogeneous structural treatment by hydrothermal treatment at 180°C for 5 hours. The mass ratio of selenium disulfide / tin diselenide complex / carbon nanotube vertical array is about 2:1, which allows Sn / S atoms to further enter the graphite lattice structure of the carbon nanotubes, causing asymmetric changes in the chemical properties of the vertical array of carbon nanotubes. Furthermore, flexible high molecular polymers (epoxy resin, polyamide resin, dimethyl phthalate) were selected and cured and packaged for the carbon nanotube vertical array in a ratio of 1:0.9:0.72. An ultrathin slicer was used to open the carbon nanotube nanoflow channels at both ends of the carbon nanotube vertical array. At the same time, in an air atmosphere, at a power of 100 watts, the sliced carbon nanotube nanoflow channels were plasma treated for 120 seconds.
[0043] Place the treated carbon nanotube nanofluidic channel as shown in the attached Figure 1 In the device, homemade Ag / AgCl electrodes were inserted into the left and right chambers of the device, and 1mmol / L potassium chloride solution was injected. At the same time, the pressure sensor was used to apply a pressure of about 100N to 500N in real time by spirally pushing the pressure application module, so that the geometric structure of the carbon nanotube nanoflow channel changed asymmetrically. At the same time, the electrochemical workstation was used to collect ion current in real time through the electrodes. As the pressure was applied, the asymmetry of the geometric structure and chemical properties of the carbon nanotubes was further highlighted. The ions in the carbon nanotube nanoflow channel were hindered and adsorbed / desorbed by the built-in electric field generated by them. Different sweeping voltages (between -10mV to +10mV and -1000mV to +1000mV) were applied by linear sweep voltammetry, and negative linearly increasing ion currents were obtained under linearly increasing voltages. The voltage is applied by a constant voltage pulse scanning method (the pulse voltage is between ±10mV and ±1000mV, and the interval time is between 10ms and 1000ms). Under the constant voltage positive and negative alternating pulses, a fluctuating negative linear increasing ion current can be obtained.
[0044] Example 4
[0045] First, using toluene and ferrocene as carbon sources (ferrocene also functions as a catalyst), a vertical array of carbon nanotubes is deposited on a silicon dioxide substrate by floating catalytic chemical vapor deposition, and the diameter of the obtained vertical array of carbon nanotubes is about 5 nanometers to 80 nanometers. Further, melamine is used as a precursor to perform heterogeneous structural treatment of the vertical array of carbon nanotubes through high-temperature heat treatment. The mass ratio of melamine / vertical array of carbon nanotubes is about 3:1. Through programmed temperature rise, it is treated at a low temperature of 300℃ to 700℃ for 2 hours, so that N atoms further enter the graphite lattice structure of the carbon nanotubes, causing the chemical properties of the vertical array of carbon nanotubes to change asymmetricly. Furthermore, flexible high molecular polymers (epoxy resin, polyamide resin, dimethyl phthalate) were selected and cured and packaged for the carbon nanotube vertical array in a ratio of 1:0.9:0.72. An ultrathin slicer was used to open the carbon nanotube nanoflow channels at both ends of the carbon nanotube vertical array. At the same time, in an air atmosphere, at a power of 100 watts, the sliced carbon nanotube nanoflow channels were plasma treated for 120 seconds.
[0046] Place the treated carbon nanotube nanofluidic channel as shown in the attached Figure 1 In the device, homemade Ag / AgCl electrodes were inserted into the left and right chambers of the device respectively, and a 10mmol / L magnesium chloride solution was injected. At the same time, a pressure sensor was used to apply a pressure of about 100N to 500N in real time by spirally pushing the pressure application module, so that the geometric structure of the carbon nanotube nanoflow channel changed asymmetrically. At the same time, an electrochemical workstation was used to collect ion current in real time through the electrodes. The schematic diagram of the test mechanism is shown in the attached figure. Figure 2 As shown. With the application of pressure, the asymmetry of the geometric structure and chemical properties of carbon nanotubes is further highlighted. Ions in the nanofluidic channel of carbon nanotubes will be hindered and adsorbed / desorbed by the built-in electric field generated by them. Different sweeping voltages (between -10mV ~ +10mV and -1000mV ~ +1000mV) are applied by linear sweep voltammetry. Under the linearly increasing voltage, a negative linearly increasing ion current can also be obtained. The constant voltage pulse scanning method is used to apply voltage (the pulse voltage is between ±10mV and ±1000mV, and the interval time is between 10ms and 1000ms). Under the constant voltage positive and negative alternating pulses, a fluctuating negative linearly increasing ion current can also be obtained.
[0047] Comparative Example 1
[0048] First, using toluene and ferrocene as carbon sources (ferrocene also has the function of a catalyst), a vertical array of carbon nanotubes is deposited on a silicon dioxide substrate by floating catalytic chemical vapor deposition, and the diameter of the obtained vertical array of carbon nanotubes is about 5 nanometers to 80 nanometers. Further, a flexible polymer (epoxy resin, polyamide resin, dimethyl phthalate) is selected to solidify and encapsulate the vertical array of carbon nanotubes in a ratio of 1:0.9:0.72, and an ultrathin slicer is used to open the carbon nanotube nanoflow channel at both ends of the vertical array of carbon nanotubes. At the same time, in an air atmosphere, at a power of 100 watts, the sliced carbon nanotube nanoflow channel is plasma treated for 120 seconds.
[0049] Place the treated carbon nanotube nanofluidic channel as shown in the attached Figure 1 In the device, homemade Ag / AgCl electrodes were inserted into the left and right chambers of the device respectively, and 1mmol / L potassium chloride solution was injected. Different sweeping voltages (between -10mV~+10mV and -1000mV~+1000mV) were applied using linear sweep voltammetry. At the same time, through the pressure sensor, the pressure application module was pushed by the spiral to apply a pressure of about 100N~500N in real time, so that the geometric structure of the carbon nanotube nanoflow channel changed asymmetrically. At the same time, the electrochemical workstation was used to collect the ion current in real time through the electrode. As the applied pressure increased, a positive linearly increasing ion current was obtained under a linearly increasing voltage. The test results are shown in the attached figure. Figure 5 The constant voltage pulse scanning method is used to apply voltage (the pulse voltage is between ±10mV and ±1000mV, and the interval time is between 10ms and 1000ms). Under the constant voltage positive and negative alternating pulses, a stable positive linear increasing ion current can be obtained. The test results are shown in Figure 6 shown.
[0050] Comparative Example 2
[0051] First, using toluene and ferrocene as carbon sources (ferrocene also functions as a catalyst), a vertical array of carbon nanotubes is deposited on a silicon dioxide substrate by floating catalytic chemical vapor deposition, and the diameter of the obtained vertical array of carbon nanotubes is about 5 nanometers to 80 nanometers. Further, melamine is used as a precursor to perform heterogeneous structural treatment of the vertical array of carbon nanotubes through high-temperature heat treatment. The mass ratio of melamine / vertical array of carbon nanotubes is about 3:1. Through programmed temperature rise, it is treated at a low temperature of 300℃ to 700℃ for 2 hours, so that N atoms further enter the graphite lattice structure of the carbon nanotubes, causing the chemical properties of the vertical array of carbon nanotubes to change asymmetricly. Furthermore, flexible high molecular polymers (epoxy resin, polyamide resin, dimethyl phthalate) were selected and cured and packaged for the carbon nanotube vertical array in a ratio of 1:0.9:0.72. An ultrathin slicer was used to open the carbon nanotube nanoflow channels at both ends of the carbon nanotube vertical array. At the same time, in an air atmosphere, at a power of 100 watts, the sliced carbon nanotube nanoflow channels were plasma treated for 120 seconds.
[0052] Place the treated carbon nanotube nanofluidic channel as shown in the attached Figure 1 In the device, homemade Ag / AgCl electrodes were inserted into the left and right chambers of the device respectively, and 1mmol / L potassium chloride solution was injected. Different sweeping voltages (between -10mV~+10mV and -1000mV~+1000mV) were applied by linear sweep voltammetry. Without applying pressure, the ion current was collected in real time through the electrode using an electrochemical workstation. As the applied pressure increased, a positive linearly increasing ion current was obtained under a linearly increasing voltage. The voltage was applied by a constant voltage pulse scanning method (the pulse voltage was between ±10mV and ±1000mV, and the interval time was between 10ms and 1000ms), and a stable positive linearly increasing ion current could be obtained under constant voltage positive and negative alternating pulses.
[0053] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A nanocurrent ion tunnel diode, characterized in that: A nanotube array with heterogeneous structure processing is disclosed. The nanotube vertical array has a nanoflow channel. There are ions in the nanoflow channel. A negative linearly increasing ion current is obtained under a linearly increasing voltage.
2. The nanocurrent ion tunnel diode according to claim 1, characterized in that: The same ion current can correspond to multiple voltage values.
3. A method for testing a nanocurrent ion tunnel diode, comprising the following steps: (1) Preparation of heterostructured nanotube vertical arrays; (2) Filling the gaps between the vertical arrays of nanotubes with flexible polymers; (3) asymmetric deformation of the vertical nanotube array by a pressure deformation device; (4) Conduct nanocurrent ion transport tests using an external static ion transport test system.
4. The testing method according to claim 3, characterized in that: The heterostructure treatment method described in step (1) includes at least one of high temperature heat treatment, hydrothermal treatment, plasma etching, and electrodeposition.
5. The testing method according to claim 3, characterized in that: The flexible high molecular polymer described in step (2) includes at least one of polydimethylsiloxane, epoxy resin, polyamide resin and silica gel.
6. The testing method according to claim 3, characterized in that: The pressure deformation device described in step (3) includes a pressure sensor, an electrolytic cell tank capable of storing a solution, and a spiral-driven pressure application module.
7. The testing method according to claim 3, characterized in that: Step (4) comprises at least one of linear sweep voltammetry, cyclic voltammetry, constant voltage pulse scanning, and alternating electric field scanning voltammetry.
8. A nanocurrent ion transport system test device, characterized in that: The invention comprises two electrolytic cell tanks capable of storing solutions, a heterostructured nanoflow channel being sandwiched between the two electrolytic cell tanks, and a through hole being provided on the contact surface between the electrolytic cell tanks and the heterostructured nanoflow channel, so that the solutions between the electrolytic cell tanks and the heterostructured nanoflow channel can communicate with each other; the left chamber and the right chamber are respectively provided with electrodes; a pressure sensor is provided on the side of one electrolytic cell tank away from the nanoflow channel, and a pressure applying module is provided on the side of the other electrolytic cell tank away from the nanoflow channel; and an ion solution is provided in the electrolytic cell tank.
9. The nanocurrent ion transport system testing device according to claim 8, characterized in that: A constant temperature water bath is respectively arranged in the two electrolytic cells.
10. The nanocurrent ion transport system testing device according to claim 8, characterized in that: The pressure applying module is a spiral-pushed pressure applying module.
Citation Information
Patent Citations
n-type zinc oxide / p-type diamond heterojunction tunnel diode and manufacturing method thereof
CN101807606A
Dynamic nanochannel and preparing and testing methods thereof
CN110527296A
Efficient carbon nanotube vertical array hybridization stripping method
CN116375005A